Senescence surveillance of pre-malignant hepatocytes limits liver cancer development - Kang, Tae-Won; Yevsa, Tetyana; Woller, Norman; Hoenicke, Lisa; Wuestefeld, Torsten; Dauch, Daniel; Hohmeyer, Anja; Gereke, Marcus; Rudalska, Ramona; Potapova, Anna; Iken, Marcus; Vucur, Mihael; et al. (Nature, 2011)
Oncogene-induced senescence has been shown to function as an intrinsic tumour suppressor mechanism. Lars Zender and colleagues now introduce the concept of 'senescence surveillance' by showing that premaligant senescent hepatocytes are cleared through a tumour antigen-directed immune response. This requires CD4+ T cells and suppresses the development of liver tumours in mouse models. The authors also provide evidence that senescent hepatocytes accumulate in the livers of immune-suppressed patients, demonstrating that senescence surveillance may also operate in humans. Strategies designed to harness antigen-specific immune surveillance of premalignant senescent cells may have potential in cancer prevention and therapy, and antigen-specific immune responses of this type may be relevant in vaccine production.
Gesehen am 11.07.2022